Plasma Diasnostic in Tokamaks Using Alfvén Waves - Manrique, Marcos Antonio Albarracin (2015)
In this work we investigated the excitation of Alfvén eigenmodes in tokamaks using external antennas to the plasma column. The basic theory of Alfvén waves is revised, including non-ideal effects such as resistivity. Then the theoretical model for excitation Alfvén waves in a cylindrical plasma column, developed by Kurt Appert, is shown in detail, as an introduction to the more complex problem of Alfvén waves in toroidal plasmas. The cylindrical model is implemented in a numerical code, which is used to study the excitation of Global Alfvén Waves (GAWs), below to the so-called Continuum of Alfvén, in TCABR and JET tokamaks, using a realistic description of their antenna systems. In the sequel, it is given a brief description of Toroidal Alfvén eigenmodes (TAEs) that are excited in the gaps of the Continuum of Alfvén created by the periodicity condition of the toroidal configuration. The excitement of these modes in JET tokamak is studied using the codes HELENA, for reconstruction of magneto-hydrodynamic equilibrium, and CASTOR, which calculates the perturbed fields in this equilibrium, coupled with instability or modes excited within the magneto-resistive hydrodynamic model. This study was carried out in order to determine, consistently, the spectrum quality and the eigenmodes associated with TAEs, with different numbers toroidal n, excited by the new JET antenna system. In particular, it was investigated in detail the effect of the phases of the supply currents of the different modules (eight) of the antenna system in the quality of the excited spectrum, using an original method, implemented in this work, based on the CASTOR code. The results indicate that, although the excitation of a certain mode may be a privileged by an optimized choice of phases, satellite modes can also be excited with higher amplitude, so that the purity of the spectrum is not substantially improved. This is the main result obtained in this work.